2021
DOI: 10.1136/bmjoq-2021-001545
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ clinical experience and its association with healthcare quality: a systematised review

Abstract: Background and purposeThere is conflicting evidence regarding whether physicians’ clinical experience affects healthcare quality. Knowing whether an association exists and which dimensions of quality might be affected can help healthcare services close quality gaps by tailoring improvement initiatives according to physicians’ clinical experience. Here, we present a systematised review that aims to assess the potential association between physicians’ clinical experience and different dimensions of healthcare qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 55 publications
(42 reference statements)
1
12
0
3
Order By: Relevance
“…51 Multiple other studies also confirm that clinical experience is not a proxy for skill or patient care quality. 25,45,[52][53][54][55][56] Our results indicate that it is not evidence based to rely on the number of procedures performed to ensure patients undergoing CRC screening undergo high-quality polypectomy procedures. SBML provides a potential solution because this method requires all learners to meet or exceed a rigorous MPS before completion of training.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…51 Multiple other studies also confirm that clinical experience is not a proxy for skill or patient care quality. 25,45,[52][53][54][55][56] Our results indicate that it is not evidence based to rely on the number of procedures performed to ensure patients undergoing CRC screening undergo high-quality polypectomy procedures. SBML provides a potential solution because this method requires all learners to meet or exceed a rigorous MPS before completion of training.…”
Section: Discussionmentioning
confidence: 87%
“…This finding is not surprising because other studies have also demonstrated that experienced practicing physicians have variable skills performance in procedures such as central venous catheter insertion, 33 temporary hemodialysis catheter insertion, 34 fundamentals of laparoscopic surgery, 38 anesthesia maintenance of certification, 37 and laparoscopic bariatric surgery 51 . Multiple other studies also confirm that clinical experience is not a proxy for skill or patient care quality 25,45,52–56 …”
Section: Discussionmentioning
confidence: 94%
“…90 This is exacerbated by polypharmacy, 91 incorrect indications, 92 and the clinical experience of prescribers. 93,94 All of which can increase hospital stays, costs, mortality, and morbidity. 95,96 This calls for an integrated multidisciplinary strategy to improve the appropriate use of antibiotics, with particular attention to extreme-aged patients with pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…However, the research on physician experience and its relationship to performance is surprisingly inconclusive. A systematic review of physician experience studies found 43% of the evaluations reviewed had a positive association, while 35% had no association and 22% showed a negative association (Ajmi and Aase, 2021). On the other hand, a review by Choudhry et al (2005) showed primarily a negative relationship between physician experience and performance, where performance reflected factual knowledge, adherence to standards of care and patient outcomes.…”
Section: Physicians' Performance In Us Hospitalsmentioning
confidence: 99%